Kilnaboy church, south window, mullion - O'Donovan, Danielle (My University, 2008)
Mullion comprising: broad central frontal fillet flanked by sunk chamfer, right-angled rebate and sunk chamfer. The rear corners of the mullion are chamfered. Close to Kilfenora Cathedral tomb niche mullion in design and geographically.
South window
Keywords: Architecture, Gothic -- Ireland; Tracery (Architecture); Late Medieval; bar tracery; mullions; moldings, hollow